Contribution of Home Industry Activities in Increasing Housewives’ Income - Rahmawati, Rina Puji (SERUNAI, 2022)
Prambatan Village, Balen Sub-district, Bojonegoro Regency has the potential for a banana debog craft home industry, but currently only makes dry debogs resembling ropes, called "ndalung". This study aims to describe the contribution of home industry activities to increase the income of housewives. The subject of the research is one of the owners of the banana debog craft home industry in Prambatan village and its workforce. This research used a qualitative approach with a descriptive method. Data collection methods used in-depth interviews, observation and documentation. Data were analyzed using the miles and huberman method. The results showed that UD home industry activities. Barokah Tani home industry activities in Prambatan Village proved a positive impact in increasing the income of housewives. Thus, the success of the positive contribution of this home industry activity has been proven in encouraging economic empowerment and increasing the income of housewives in Prambatan Village.